Impact of Non-Performing Loan on Profitability of Nepalese Commercial Banks - Shrestha , Purna Man; Khadka, Kamal Kumar (Researcher CAB: A Journal for Research and Development, 2024)
This paper aims to evaluate the impact of non-performing loan on the profitability of Nepalese commercial banks. For this purpose, this study employed the annual balanced panel data of 10 commercial banks during the period of 2016/17 to 2022/23. This paper used NPLs measured by the ratio of non-performing loans to total loans as an explanatory variable and profitability measured by ROA as a dependent variable. A multiple linear regression model was used to examine the effect of NPLs on the profitability of banks. The empirical results indicated that NPLs play a substantial role in determining profitability. Further, this paper revealed that NPLs have a significant negative impact on profitability. The findings of this paper suggests that bank management should maintain the lower level of NPLs as much as possible to achieve a higher level of profitability. Therefore, bank management should give more attention to minimize the NPL.